Multicenter Study of the Hemorrhage Risk after Endoscopic Mucosal Resection Associated with Direct Oral Anticoagulants. (18th December 2019) - Yasuda, Ritsu; Yoshida, Naohisa; Murakami, Takaaki; Hirose, Ryohei; Inoue, Ken; Dohi, Osamu; Naito, Yuji; Inada, Yutaka; Okuda, Takashi; Hasegawa, Daisuke; Okuda, Kotaro; Ogiso, Kiyoshi; et al.
Abstract : Backgrounds and Aims . Recently, direct oral anticoagulants (DOACs) have become widely used for preventing thromboembolism. However, postoperative hemorrhage (POH) is a major complication associated with endoscopic mucosal resection (EMR) for colorectal lesions. In this multicenter study, we analyzed the incidence of POH after EMR associated with DOACs and explored the associated risk factors. Materials and Methods . This study was a multicenter retrospective cohort study conducted at 8 Japanese institutions. A total of 2062 cases that underwent EMR for colorectal lesions at these 8 institutions from October 2016 to September 2017 were analyzed. The cases were divided into 4 groups: the DOAC group (63 cases), warfarin group (34 cases), antiplatelet group (185 cases), and no antithrombotics group (1780 cases). In all lesions of the DOAC and warfarin groups, endoscopic clipping was performed after EMR. The rate of POH in the DOAC group, patients' clinical characteristics, the risk factors of POH, and the rate of thromboembolism due to stopping DOACs were compared with other groups. Results . The rates of POH were 7.9% ∗ (5/63), 2.9% (1/34), 3.2% (6/185), and 0.6% ∗ ∗ (11/1780) in the DOAC, warfarin, antiplatelet, and no antithrombotics groups, respectively ( ∗ vs. ∗ ∗, p < 0.001 ). Regarding risk factors, the tumor size with POH (mm) was significantly bigger than that without POH (16.2 ± 8.3 vs. 7.2 ± 4.9, p < 0.001 ). There were no significant differences in the rates of POH based on the type of DOAC. In addition, no thromboembolisms occurred due to stopping of DOAC treatment. Conclusions . Patients receiving DOACs had significantly higher rates of POH after EMR than those without antithrombotics.